2012
DOI: 10.2478/s13531-011-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations for optimization of neutron shielding concrete

Abstract: Concrete is one of the main materials used for gamma and neutron shielding. While in case of gamma rays an increase in density is usually efficient enough, protection against neutrons is more complex. The aim of this paper is to show the possibility of using the Monte Carlo codes for evaluation and optimization of concrete mix to reach better neutron shielding. Two codes (MCNPX and SPOT -written by authors) were used to simulate neutron transport through a wall made of different concretes. It is showed that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 12 publications
2
15
0
4
Order By: Relevance
“…One more conclusion is that changing amount of Ba in wide area has no influence on shielding efficiency. It is in agreement with preliminary studies made by Piotrowski et al [24]. It is clear that the most activated concretes had a large amount of iron.…”
Section: Monte-carlo Aided Design Of Neutron Shielding Concretessupporting
confidence: 82%
See 1 more Smart Citation
“…One more conclusion is that changing amount of Ba in wide area has no influence on shielding efficiency. It is in agreement with preliminary studies made by Piotrowski et al [24]. It is clear that the most activated concretes had a large amount of iron.…”
Section: Monte-carlo Aided Design Of Neutron Shielding Concretessupporting
confidence: 82%
“…The presented results are the second step of the research program. The first were the simulations on shielding of theoretical composition of concretes in a theoretical neutron flux [24]. In this paper there have been simulated shielding and activation of real concretes from nuclear facilities in a theoretical neutron flux.…”
Section: Discussionmentioning
confidence: 99%
“…The source was simulated inside the sample and the outer surface was treated as a detector. First MCNP simulations were performed for a neutron flux from a light water reactor (LWR) core with total flux of 4.64 × 10 9 n/(cm 2 s) calculated using APOLLO 2 [4]. By the use of this neutron source first the influence of gadolinium oxide content in 1, 2 and 5% in relation to cement was analysed by the comparison of neutron flux on the different levels of energy counted in the detector.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary studies of Piotrowski et al [4] were based on Monte Carlo computer simulations and it was indicated that both the compressive strength and type of concretes (normal and heavy-weight) have a significant effect on the shielding against neutron. It was concluded that the decrease in the neutron dose detected behind the concrete shielding was proportional to the concrete (B-9) strength and an increase in the cement content in the mixture and the associated mass of bound water as a result of its hydration.…”
Section: Introductionmentioning
confidence: 99%
“…First studies carried out by Piotrowski et al [9] in this field using Monte Carlo computer simulations indicate that both the compressive strength and type of concrete have a significant effect on the shielding against neutron. The decrease in the dose is proportional to the strength and an increase in the cement content and the associated mass of bound water as a result of its hydration.…”
Section: B-15 Frommentioning
confidence: 99%